Computation of the Complexity of some Recursive Constructed Normal Polynomials - Alizadeh, Mahmood (Mathematical Problems of Computer Science, 2021)
In this paper we give some algorithms for computing the complexity of some normal polynomials constructed by some recurrent methods. Finally some results of our algorithms are given in a table.